Epoxy and aziridinyl enolsilanes in diastereoselective inter- and intramolecular Friedel–Crafts alkylations. Issue 4 (19th February 2016) - Ling, Jesse; Lam, Sze Kui; Lo, Brian; Lam, Sarah; Wong, Wing-Tak; Sun, Jian; Chen, Guanhua; Chiu, Pauline
Abstract : Diastereoselective Friedel–Crafts reactions of optically pure epoxy enolsilanes afford enantiomerically-enriched β-hydroxy-α-arylketones. Aziridinyl enolsilanes react in an analogous manner. Abstract : The Friedel–Crafts alkylations of epoxy enolsilanes with arenes occur under silyl triflate catalysis at low temperatures. Intermolecular alkylations with optically-enriched epoxides occur with conservation of ee. Intramolecular reactions give rise to cyclized products with high diastereoselectivity in good yields. Aziridinyl enolsilanes also undergo selective inter- and intramolecular Friedel–Crafts reactions in a similar manner.